The future of branding - Srivastava, Rajendra K.; Thomas, Gregory Metz (SAGE Publications, 2016)
"New ideas change the world. From social movements to scientific discovery the power of an idea is to reshape the world, who we are, and how we live. Changes in the increasingly dynamic competitive environment require a focus on what should be done, not just what is currently done. The inspiration for this book is to provide an outlet for cogent ideas that will help managers build and maintain brands in the future marketplace. Written by the leading minds management from around the globe who are redefining best practices in managing brands, It examines the future of branding on key concepts including brand performance management, brand strategy, brand building, revitalizing brands, brand valuation, brand analysis, brand protection, and brand experience"--Provided by publisher.